Free will between Slavery and Freedom: A Study of Linda Brent in Incidents in the Life of a Slave Girl by Harriet Jacobs (Journal of the College of Languages (JCL), 2022)
Harriet Jacobs was a writer and a reformer. As a female writer in the nineteenth century, Jacobs wrote her narrative as a means of resisting the system of slavery. She wrote her book Incidents in the Life of a Slave Girl: Written by Herself, (1842) to reflect upon the exploitation of the black people and the need to change the hierarchal attitude that governs white/black relations. She was engaged in many abolitionist events and her anti-slavery approach appeared clearly in her writings. She shares Du Bios ideas about freedom and emancipation and the need for a political and cultural change. Thus, Du Bois’s theory provides a framework for her autobiographical novel where she portrays Linda Brent, the main character, a strong willed lady whose path to freedom came after an agonizing journey. Despite differences in cultural status and upbringing, both of Jacobs and Du Bois go from a subjective representation of a personal experience to an objective statement about the general conditions of black people in slavery, and the discrimination black people face during their lives. To Jacobs, freedom is a choice a person has to fight for, and a mental process that is accomplished through resistance and protest. Her strategies of resistance came through three points in the novel; the family, who helped her through her journey; pregnancy and the choice of the father of her kids; and finally motherhood and the promise of a better future for her children. This paper concludes that Jacobs’s novel is a narrative antecedent for slaves’ voices and a reclamation of identity after slavery.